Ancient specimens and DNA contamination: a case study from the 12S rRNA gene sequence of the "Linh Duong" bovid (Pseudonovibos spiralis) - Hassanin, Alexandre (Die Naturwissenschaften, 2002)
In 1993, several unusual horn sheaths, collected in the South of Vietnam, were regarded as evidence for a new mammal species, Pseudonovibos spiralis. However, the taxonomic status of P. spiralis remains a highly controversial subject: firstly, it has been related to three different groups of the family Bovidae: Antilopini (gazelles), Bovini (oxen, bisons, and buffaloes), and Caprini sensu lato (goats, sheep and allies). Secondly, certain horns have been shown to be faked. Most recently, it has been suggested, on the basis of 12S rRNA gene sequences, that P. spiralis was a new species of buffalo. I demonstrate here that this conclusion was inaccurate, and base this on the grounds that: (1) the putative sequence of P. spiralis is shown to be a chimera obtained from three different species: Bos taurus, Bubalus bubalis and Saiga tatarica, and (2) several factors indicate that the specimen used was not authentic. This new study confirms earlier suggestions that the horns used to formally describe P. spiralis were bogus and were in fact derived from the horns of domesticated cattle (Bos taurus). The data suggest that P. spiralis never existed.